COMBINED VACCINE IS AN EFFECTIVE AND SAFE PROTECTION FROM FIVE CONTROLLABLE INFECTIONS - D. A. Novikova; N. E. Tkachenko (Педиатрическая фармакология)
The article is dedicated to prevention of controllable infections in infants. This is an urgent issue, as up to 40 mln. infectious diseases are registered in Russia every year; infections are particularly prevalent in children. Infectious pathologies may take up to 70% of all health conditions in children. Vaccination is the only effective method of preventing infectious diseases. The authors present international experience of using a pentavalent vaccine, which contains diphtherial and tetanus toxoids, acellular pertussis component, inactivated poliovirus and type b Haemophilus influenzae polysaccharide. This vaccine is included into immune prevention schedules for children of 0-1 (primary vaccination) and 1-2 (revaccination) years of age in many countries. The article presents results of major clinical studies, which confirm low reactogenicity and high effectiveness of the mentioned vaccine.